SISTEM PENDUKUNG KEPUTUSAN BEASISWA SEKOLAH TINGGI ILMU AGAMA BUDDHA SMARATUNGGA - Hayat, Latiful; Wahyuni, - (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2010)
Someone who has right to get scholarship is someone who has passed some selected criteria. Eachcriteria has level which different to each other. Depends on the level from each criteria, can be got by levelable to be short according to selected priority.Data processing which required many consideration will felt difficult and need very long time if doneby manual, any else if the data reach millions. A decission support system based on computer which cangive support to the process of determination of grantee student can support data processing process Thissystem give decision choice alternatives pursuant to degree of membering its’ variable that used in decisionmaking process.Determination of eligibility of student to get scholarship is done to phase selection where which usedas consideration is in achievement student semester, storey level, production of old fellow of student, amountof the lack of administration burden which not yet fulfil by student, existence of achievement of life line ofstudent lecturing and also special priority which given by college theology of Buddha Smaratungga tostudent because selected things like student that on his area happen a natural disaster.Determination of eligibility poured into degree of membership for each variable. The next phase is hecalculation degree recommended pursuant to criteria and condition determined by the provider ofscholarship through the combination of how big the degree of membership from each selected variable.Keyword : Decission support system, scholarship